(untitled) (Journal of the College of Basic Education, 2022)
The research aims to prepare a sandy playground in the school yard for the purpose of training on it. And to know the effect of the sand court in developing some physical abilities. And to know the effect of the sand court in developing some basic skills. The researcher used the experimental one-group approach to suit the nature of the problem. The community and the sample were deliberately chosen, and they are the 22 female secondary school players. The training curriculum was applied to the research sample on Tuesday 19/11/2019 and ended on Thursday 1/9/2020, and after collecting the data, it was processed statistically and the following conclusions emerged : The sand court has a direct impact on the development of the physical capabilities of the subject of study. The sand court had a direct effect on the development of the skills abilities in question. The sand court has proved its worthy football.